Expanded PCR panel for uropathogen identification and treatment recommendations in urinary tract infections - Lindsey Leech; Christopher Bigley; Marshall Chew; Ashley Crawford; JeanAnn Vawter; Manish P. Patel (Therapeutic Advances in Urology)
Background: Urinary tract infections (UTI) are common and costly, but standard urine culture (SUC) diagnostic tests have significant limitations. Emerging molecular techniques like multiplex polymerase chain reaction (PCR) offer rapid simultaneous detection of uropathogens and antimicrobial resistance (AMR) genes allowing timely targeted therapy. Objectives: To compare the performance of Urine-ID™ test, an expanded multiplex PCR panel designed to detect 26 uropathogens and 49 AMR markers against SUC for pathogen detection in individuals with suspected complicated UTI. Design and methods: A total of 56 urine specimens from individuals aged 50 and older, who exhibited UTI symptoms and failed previous therapy based on SUC results, were retrospectively analyzed using Urine-ID ™ using the TaqMan ® OpenArray plates on the QuantStudio 12K Flex Real-Time PCR System. Results of simultaneously collected PCR and SUC were compared at patient follow-ups. Results: Of the 56 suspected UTI cases, SUC failed to detect pathogens in 19.64% ( N  = 11/56) of the specimens while PCR yielded negative results in 7.14% ( N  = 4/56) of cases. SUC identified a specific organism in 50% ( N  = 28/56) while PCR detected at least one uropathogen in 92.86% ( N  = 52/56) of specimens. Data also revealed that a nonspecific result, “Mixed urogenital flora” (MUG), was the most frequent outcome ( N  = 18/45) obtained with SUC among positive samples. While SUC identified a single pathogen in 92.80% ( N  = 26/28) of positive specimens, PCR detected additional co-infecting uropathogens in 71.20% ( N  = 37/52) of positive samples. Of the 18 MUG and 11 negative samples using SUC, PCR identified treatable pathogens in 13 and 7 samples, respectively. Conclusion: These results highlight the effectiveness of expanded real-time PCR panels for quickly and accurately identifying uropathogens, surpassing traditional SUC sensitivity. Adopting these advanced molecular techniques, particularly in suspected complicated UTI cases, improves diagnosis efficiency, leading to faster pathogen identification and treatment, ultimately reducing patient morbidity.